2012 International Conference on Information Security and Intelligent Control 2012
DOI: 10.1109/isic.2012.6449770
|View full text |Cite
|
Sign up to set email alerts
|

A modified probability neural network indoor positioning technique

Abstract: This paper presents an indoor positioning technique using a modified probabilistic neural network (MPNN) scheme. It measures the received signal strength (RSS) between an object and stations, and then transforms the RSS into distances. A MPNN engine determines coordinate of the object with the input distances. The experiments are conducted in a realistic ZigBee sensor network. The proposed approach performs significantly better than triangulation technique when the RSS data are unstable. It can be efficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In the performing stage, mobile stations can detect the RSSIs of neighbor base stations and Wi-Fi APs, which can be adopted in the trained models to estimate the locations of these mobile stations. of estimated locations by the method were higher than those by the triangulation technique [11]. An improved neural network was trained with the correlation of the initial parameters to achieve the highest possible accuracy of the Wi-Fi-based positioning method in indoor environments [8].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the performing stage, mobile stations can detect the RSSIs of neighbor base stations and Wi-Fi APs, which can be adopted in the trained models to estimate the locations of these mobile stations. of estimated locations by the method were higher than those by the triangulation technique [11]. An improved neural network was trained with the correlation of the initial parameters to achieve the highest possible accuracy of the Wi-Fi-based positioning method in indoor environments [8].…”
Section: Related Workmentioning
confidence: 99%
“…For LBS in indoor environments, Wi-Fi-based positioning methods are popular techniques to detect and analyze the received signal strength indications (RSSIs) from Wi-Fi access points (APs) [5,8,[10][11][12][13][14][15][16][18][19][20][21]. The fingerprinting positioning methods based on machine learning algorithms were proposed to learn the relationships among locations and RSSIs for the estimation of locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [21] pioneered the use of the probabilistic distribution measurement in IPS and proposed a probabilistic framework by using the Bayesian network to estimate the location. In [22] the authors used a modified probability neural network (MPNN) to estimate the coordinates of the object and found that it outperformed the triangulation method. In [23], a kernel method was proposed to estimate the object's location using a histogram of the RSSI at the unknown location.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the appropriate NN structure ensures more adequate interpretation of measurements. Chen, Yin, Chen, and Hwang present an indoor localization system with a Modified Probabilistic Neural Network operating in ZigBee network [15]. The system is designed to estimate an object's position with distorted RSS.…”
Section: Survey Of Related Workmentioning
confidence: 99%